SIKAP MUSLIM TERHADAP MURTAD DALAM PERSPEKTIF AL-QUR'AN - Zakaria Syafe'i (Al Qalam, 2011)
Islam gives human freedoom to profess a religion without any coercion. This freedom principle includes when one want to convert from his previous religion into another one. In Islam, it is called riddah, leaving Islam to convert into another religion consciously. The performers of riddah are called the apostates.The action of Riddah is fulminated by the Qur'an; however, the Qur'an does not clearly determine the punishment far the apostates. The majority of Islamic law scholars classify riddah as Jarimah (an injustice deed) that must be under pain of death as stated in hadits. Such a classification breaks the rights of the liberty of conscience supported by several verses of the Qur'an.The death penalty that is applied to the Jarimah performers, as a matter of fact, does not spontaneously apply when the action of Jarimah is known, but there is resuscitation process by persuading the apostates to reconvert into Islam. Moreover, the ulamas have different opinions in determining the criteria of Jarimah riddah (the criminal law of apostasy) that causing the death penalty. In this case, there is contradiction between the Qur'an and hadits. Therefore, the decision of the death penalty far the apostates should be reviewed. Key Word : riddah, Islam, criminal law, death penalty